Poincare's Theorem of Asymptotic Series and its Application - Kumar, Nand Kishor; Yadav, Dipendsra Prasad; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2024)
This article explains an important asymptotic series theorem. Poincare also demonstrates how to solve linear differentials with polynomial coefficients using asymptotic series. The significance of asymptotic series has also been discussed.